2014
DOI: 10.24908/ijsle.v0i0.5579
|View full text |Cite
|
Sign up to set email alerts
|

Service Learning: A Bridge to Engineering for Underrepresented Minorities

Abstract: Female, Black, Latino and Native American students are underrepresented in the STEM pipeline. Finding ways to increase underrepresented populations in STEM fields continues to be a major initiative in education. Many underrepresented student groups express a strong orientation toward service and community engagement. Informal Science Education (ISE) can be structured to include community engagement and to engage learners’ interest and enhance their understanding of the theory and practice of science. Service l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…This may be why CEL attracts females at a rate three times that of their male counterparts. A similar trend has been noted for other underrepresented populations in engineering, such as African Americans, Latino/Latinas, and Native American [5][6][7][8][9][10][11]. Furthermore, Zarske, et al found that project-based CEL design experiences have a significant positive impact on the identity and self-efficacy of all students, but a greater impact on women and minority students when compared to Caucasian males [7].…”
Section: Introductionsupporting
confidence: 56%
See 2 more Smart Citations
“…This may be why CEL attracts females at a rate three times that of their male counterparts. A similar trend has been noted for other underrepresented populations in engineering, such as African Americans, Latino/Latinas, and Native American [5][6][7][8][9][10][11]. Furthermore, Zarske, et al found that project-based CEL design experiences have a significant positive impact on the identity and self-efficacy of all students, but a greater impact on women and minority students when compared to Caucasian males [7].…”
Section: Introductionsupporting
confidence: 56%
“…It is well established that the United States (US) has a need for enhanced participation as well as increased racial and gender diversity in the Science, Technology, Engineering and Mathematics (STEM) fields, particularly engineering [1][2][3][4]. Farinde, Tempest and Merriweather (2014) report that careers that are perceived to help humanity with high levels of community engagement may be more attractive to African American, Latino/Latina, Native American and females [5]. Engineering Community Engaged Learning (CEL) is an excellent way to help those involved in these experiences to understand how engineering, as well as other STEM careers, can have a high level of community engagement, can be used to help humanity, require creativity and are personally rewarding careers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of 120 reviewed articles, 49 (40.8%) mentioned that students made international travel to conduct their community engagement projects in other countries (e.g., Johnson & Johnson, 2008;Lewis et al, 2016). Time constraint was an important factor affecting students' community engagement: 21 articles had mentioned it (e.g., Farinde et al, 2014;Lewis, 2014). For community engagement to be educative, considerable time should be involved (Kolb, 1984).…”
Section: Logistics Constraintsmentioning
confidence: 99%
“…This type of program was implemented by Farinde, Tempest and Merriweather in 2014, in the United States [11]. The program called Bridge to Engineering was planned as an ISE (Informal Science Education) for underrepresented high school students with engineering students as mentors [11].…”
Section: Educational Project-based Community Servicementioning
confidence: 99%